Tailored recovery of nutrients from the anaerobic membrane bioreactor (AnMBR) resource recovery platform and their subsequent beneficial reuse - Damodara Kannan, Arvind (Kansas State University, 2022)
Agriculture runoff, animal farming wastewater, and processed livestock wastes contain high concentrations of nutrients and organic matter. There is a great potential to recover the nitrogen and phosphorus from agriculture wastewater as stabilized sludge biosolids or value-added Recovered Nutrient Products (RNPs) in the form of ammonia nitrogen and/or phosphorus (P) mineral precipitates, using suitable treatment technology. This research aims to demonstrate tailored recovery of valuable macronutrients like Nitrogen and Phosphorus from anaerobic environmental biotechnology platforms such as Anaerobic Membrane Bioreactors (AnMBR) treating swine wastewater from confined animal feeding operations (CAFOs) for targeted reuse as fertilizer products. The first objective of this study was the recovery of ammonium (NH₄⁺) from real swine wastewater and simulated AnMBR treated swine permeate using natural clinoptilolite. Batch experimental results showed a maximum adsorption capacity of 14 mg N/g clinoptilolite from synthetic swine permeate. Column experiments revealed that the breakthrough times for the real swine and synthetic swine wastewaters to be similar indicating that the wastewater matrix did not really have an effect on ammonia adsorption. Ion release profiles showed sodium to be the main counter ion for ammonium capture. The presence of potassium ion had the greatest impact on ammonia adsorption and the selectivity series was summarized to be Potassium (K⁺) > Calcium (Ca²⁺) > Sodium (Na⁺) > Magnesium (Mg²⁺). The second objective was to identify the core microbial community in Anaerobic sludge for beneficial soil application as stabilized biosolids. Results revealed that the core of the AnMBR microbial community represented by Bacteroidetes, Proteobacteria, Firmicutes, and Chloroflexi phyla is unique and not influenced by the influent wastewater microbial community. The AnMBR microbial community structure not only enables proactive ecological management for efficient bioreactor operation but also informs the potential microbial interactions with the soil microbiota for beneficial land/crop application. The third objective aims to evaluate the ammonia sorbed clinoptilolite and anaerobically treated biosolids for cropland application and plant nutrient bioavailability. Soil incubation studies showed that the ammonia sorbed clinoptilolite exhibited slow nitrogen diffusion compared to conventional fertilizers such as urea and ammonium sulfate. However, biosolids obtained after anaerobic digestion of wastewater showed negligible nutrient release, likely due to slow mineralization of organic nitrogen over the duration of this study. In view of these results, additional greenhouse pot experiments were conducted with maize crop to evaluate plant nitrogen uptake with ammonia sorbed clinoptilolite as a supplement to urea application and possibly to reduce the urea application rate. Treatments included 100% urea, 90% urea+10% ammonia sorbed clinoptilolite mixture, 80% urea+20% ammonia sorbed clinoptilolite mixture, and 100% ammonia sorbed clinoptilolite. The treatments were compared for plant nitrogen uptake, total dry biomass, and leaf chlorophyll content. The results on plant dry biomass and leaf chlorophyll content showed no statistically significant difference between the different treatments, suggesting that the ammonia sorbed clinoptilolite can be used as a nitrogen supplement, effectively reducing nitrogen losses from urea. The fourth objective of this dissertation aims to demonstrate sustainable recovery of phosphorus as high-quality calcium phosphate from anaerobic membrane bioreactor treated swine permeate for targeted use as fertilizer or raw material for the fertilizer industry. Phosphorus removal efficiencies from treated swine permeate were evaluated by adding various calcium/phosphorus molar ratios ranging from 1/1 to 12/1. Results showed that removal efficiencies were inconsistent in duplicate trials at the same calcium doses (maximum P removal 93 % in Trial 1 and <20 % removal in Trial 2). The variability in P removal was due to the high bicarbonate alkalinity of the swine permeate, which buffered the system and thereby prevented it from reaching alkaline pH conditions ideal for P removal. Total alkalinity and initial solution pH had the greatest impact on P removal and caused unintended precipitation of non-specific calcium minerals (Calcite). The carbonate alkalinity from the permeate was removed using process modifications that included acid addition and aeration for stripping the CO₂. Carbonate removal resulted in 97% P removal with increased total P content (11.8% P) in the final product and its better solubility. Additional COD removal (~18%) was also observed during the flocculation process. Finally, sequential recovery of phosphorus as struvite (MgNH₄PO₄.6H₂O) and calcium phosphate in the pH altered CO₂ stripped swine permeate was also investigated. The results of the preliminary test run conducted at pH 9.5, showed a P removal efficiency of 56.4% after Magnesium (Mg) addition at a Mg/P molar ratio of 2/1, followed by 40.9% P removal after Calcium (Ca) addition (Ca/P molar ratio of 4/1) resulting in a combined P removal efficiency of 97.3 %. Phase identification of the solid precipitate collected after Mg addition showed the presence of struvite mineral. Similar experiments performed at a pH of 8.5 showed a maximum combined P removal of 61%, with 15% P removal after Mg addition and 46.2 % P removal after Ca addition. These results showed that P can be effectively recovered from the modified swine permeate as tailor-made products such as struvite and calcium phosphates sequentially. Overall, the results of this dissertation demonstrate that AnMBRs can be a sustainable nutrient recovery platform enabling tailored recovery of nutrient products with commercial value. Additionally, the ammonia captured clinoptilolite can be used as a soil amendment to supplement conventional fertilizers and avoid their over application.
Keywords: Resource recovery; Wastewater treatment; Nutrient recovery; Circular economy; Phosphorus recovery; Sustainability